Preparation of Raw Materials for Knitted Products from Natural Silk - J. Akhmedov; Kh. Alimova; T. Tursunov; Q. Sabirov; G. Umarova (Research Parks Publishing LLC, 2022)
The article presents the evaluation indicators by selecting raw silk for the manufacture of knitted products, comparing its quality. Raw silk from Navruz-1 and Chinese hybrids, which are currently grown in the country, was used to make yarn. The technology of making twisted yarns for use in knitting has been proposed. In order to ensure the softness and elasticity of the spun yarns, a recipe for boiling them is recommended. The amount of residual sericin was calculated taking into account the properties of the added yarns and the value of a certain degree of growth, the reduction of sericin content in the yarn during boiling has a sharp effect on their ability to withstand various repetitive stresses of geometric dimensions, uniformity, mechanical properties. The strength characteristics of the spun yarns before boiling and after removal of the sericin are given. Since the initial recommended 350 tw/m values did not fully provide strength, it was found that the requirements for it were fully met when the number of turns was increased by 25%. One of the main technological features of raw silk is the ability to rewind from yarn to spool, which affects its quality, cost and the appearance of the rings. The raw silk used for the production of knitted products was inspected by organoleptic method before testing the condition of the yarns, and a special emulsion was sprayed on the yarns with the sticky parts. The ability to rewind raw silk was tested on a rewinding machine MT-85 (Japan) at a speed of 140-5 m / min. It was rewrapped for 90 minutes in accordance with the requirements of the standard, taking into account the rings.